Objective pain sensitivity affects sleep quality in opioid dependent males on methadone maintenance therapy - Nasir, Mohamad; Zalina, Zahari; Siong Lee, Chee (2014)
Aim Pain associated poor sleep quality has been reported among opioid dependent patients on methadone maintenance therapy (MMT) but objective pain data are lacking. This study aimed to investigate the rate of objective pain sensitivity and the relationship between pain sensitivity and sleep quality in this susceptible male population. Methods A total of 168 male patients from MMT clinic in Kelantan, Malaysia were included into the study. Objective pain tolerance to cold pressor test (CPT) was evaluated at 0 hour and at 24 hours after the first CPT. Malay version of the Pittsburgh Sleep Quality Index – PSQI and the subjective opiate withdrawal scale (SOWS) questionnaires were administered to evaluate the quality of sleep and withdrawal symptoms, respectively. Results The mean age of the study participants was 37.22 (SD 6.20) years old. The mean daily methadone dose was 76.64 (SD 37.63) mg/day. The mean averaged SOWS score was 5.43 (SD 6.91). The averaged pain tolerance time ranged from 7 to 300 s with a mean time of 32.16 (SE 2.72) s, slightly below the cut-off score of 37.53 s. More specifically, 78.6% (n = 132) of patients were identified as ‘pain-sensitive’ (averaged pain tolerance time ≤ 37.53 s), and 36 (21.4%) were ‘pain-tolerant’ patients (averaged pain tolerance time > 37.53 s). The mean global PSQI score was 5.47 (SD 2.74). The pain-sensitive patients reported poorer sleep quality with mean (SD) of 5.78 (2.80) compared with pain-tolerant patients with mean (SD) of 4.31 (2.18) (p = 0.005). With analysis of covariance, pain-sensitive patients were found to have higher global PSQI scores (adjusted mean 5.76, 95% CI 5.29; 6.22) than pain-tolerant patients (adjusted mean 4.42, 95% CI 3.52; 5.32) (p = 0.010). Conclusions Many opioid dependent male patients on MMT are pain-sensitive. A poorer sleep quality is associated with objective pain sensitivity. Pain and sleep complaints in this susceptible population should not be overlooked.